Penyuluhan Deteksi Dini Kanker Leher Rahim Metode Tes IVA Pada Wanita Usia Subur di Desa Muaratais Tahun 2020 - Daulay, Suryani Agustina (Universitas Aufa Royhan Di Kota Padangsidipuan, 2025)
Cervical cancer is the most common cancer in women with 7.5% of all deaths due to cervical cancer. Cervical cancer is still found in many developing countries, including Indonesia. The aim of this PKM is to motivate women of reproductive age (WUS) about the importance of early detection of cervical cancer using the IVA test method. PKM activities were carried out by means of health education methods using leaflet media to 30 WUSs in Muaratais Village. The results of this outreach activity were continued by providing an evaluation to WUS, namely questions and answers regarding the material on early detection of cervical cancer using the given IVA test method. There were three questions that were asked by the extension agent to WUS. Based on the answers given, the WUS showed that the WUS understood the material provided by the extension agents. PKM activities carried out went well. The WUS in Muaratais Village who participated in the activity seemed enthusiastic about participating in the counseling activities.